A Secured Model of IoT-based Smart Gas Detecting and Automatic Alarm System - Methila Farzana Woishe; Nila Sultana; Tamanna Zaman Bristy; Nafiza Anjum Khan; MD. Taimur Ahad (Institut Teknologi Bisnis AAS Indonesia, 2022)
A gas leakage detector is a device for detecting gases in an area that is often used in a security system. This type of equipment is used to detect gas leakage or another emission. A gas warning device can alert operators in the vicinity of a possible gas leak and enable them to escape. The device is important because many gases can be harmful to organic life, such as humans or animals. This can be used to detect flammable, flammable, and toxic gases, as well as a lack of oxygen. Identifying potentially dangerous gas leaks through sensors. These sensors often use an audible alarm to alert people when dangerous gas has been detected. The purpose of this paper is to propose and discuss the design of an IoT-based gas leakage detection system that can automatically detect and warn gas leaks. The proposed system also includes a warning system for users. The system is based on sensors that can easily detect gas leaks.